2022
DOI: 10.3390/microorganisms10050907
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Invasive Neisseria meningitidis and Haemophilus influenzae Infections in France during the COVID-19 Pandemic

Abstract: BackgroundSince the appearance of COVID-19 in January 2020, invasive bacterial infections have decreased significantly worldwide. However, alterations in age and sex distributions, clinical forms, phenotypes, and genotypes of isolates have not been analyzed. Our goal is to present and discuss these data considering the current COVID-19 pandemic situation. Methods: The data of the national reference center for meningococci and Haemophilus influenzae in France were mined to examine the above aspects of invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
(24 reference statements)
2
21
1
1
Order By: Relevance
“…Asplenia, agammaglobulinemia and deficiencies of early complement components (e.g. C1-C3) are also related to the risk of invasive infections caused by H. influenzae [1]. In our case we did not detect such abnormalities.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Asplenia, agammaglobulinemia and deficiencies of early complement components (e.g. C1-C3) are also related to the risk of invasive infections caused by H. influenzae [1]. In our case we did not detect such abnormalities.…”
Section: Discussioncontrasting
confidence: 69%
“…Nevertheless, non-typeable strains of H. influenzae can lead to invasive infections [1]. A prospective cohort study of 80 adult cases of H. influenzae meningitis published in 2021 in the Netherlands has shown that in adult patients, the majority of H. influenzae meningitis occurs with non-typeable strains [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations